2002
DOI: 10.1253/circj.66.185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Class III Antiarrhythmic Agent, NIP-142, on Canine Atrial Fibrillation and Flutter

Abstract: The effects of a new benzopyran derivative, NIP-142, on atrial fibrillation (AF) and flutter (AFL) and on electrophysiological variables were studied in the dog. NIP-142 (3mg/kg) was administered intravenously to pentobarbital-anesthetized beagles during vagally-induced AF and during AFL induced after placement of an intercaval crush. Isolated canine atrial tissues were studied using standard microelectrode technique. NIP-142 terminated AF in 5 of 6 dogs after an increase in fibrillation cycle length (CL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
1
34
0
2
Order By: Relevance
“…6 Several experimental I Kur blockers are under investigation. 7,8 One of them (AVE0118), which, in addition to I Kur , blocks the I to current, is evaluated in the present study. We hypothesized that in electrically remodeled atria, blockade of the early repolarizing currents restores the plateau of the action potential, thereby exerting an antifibrillatory effect.…”
mentioning
confidence: 99%
“…6 Several experimental I Kur blockers are under investigation. 7,8 One of them (AVE0118), which, in addition to I Kur , blocks the I to current, is evaluated in the present study. We hypothesized that in electrically remodeled atria, blockade of the early repolarizing currents restores the plateau of the action potential, thereby exerting an antifibrillatory effect.…”
mentioning
confidence: 99%
“…The ERP prolongation by NIP-142 was greater in the presence of VNS than normal condition (Nagasawa et al, 1999). We also reported that this compound at 3 mg/kg prolonged atrial ERP by about 20 ms under VNS, but at doses up to 10 mg/kg it had no significant atrial ERP prolongation effect without VNS .…”
Section: Effects Of Nip-142 On Af Modelsmentioning
confidence: 49%
“…Injection of NIP-142 (3 mg/kg) terminated AF after increase in fibrillation cycle length and prevented reinitiation of AF in VNS-induced model. This compound terminated macroreentry type of atrial flutter induced after placement of an intercaval crush without affecting atrial flutter cycle length (Nagasawa et al, 1999). NIP-142 prolonged atrial ERP by about 10% without affecting intraatrial and interatrial conduction times in these models, which suggested that the antiarrhythmic effects were achieved by the atrial ERP prolongation.…”
Section: Effects Of Nip-142 On Af Modelsmentioning
confidence: 86%
See 1 more Smart Citation
“…This compound terminated the canine vagal stimulation-induced atrial fibrillation and canine Y-shaped incision-induced atrial flutter (7). These effects have been attributed to prolongation of atrial refractory period.…”
Section: Introductionmentioning
confidence: 91%